Multi Analysis of the Roots of Extremist Thought and Islamic Solutions through the Concepts of Tasamuh and Ukhuwah Wathaniyah - Najamudin Najamudin; Muhammad Kodri Kostolani; Azmi Ubaidillah Yusril (Civilization Research: Journal of Islamic Studies, 2026)
The phenomenon of religious extremism and radicalism currently poses a serious challenge to social stability and national harmony in Indonesia. This ideology often stems from a narrow, rigid, and exclusive understanding of religion, which, if left unchecked, can undermine national integration and trigger horizontal conflicts. This study aims to analyze the roots of extremist thinking, its impact on interfaith harmony, and how these ideologies represent deviations from religious doctrine. In addition, this study seeks to offer strategic solutions through the concept of religious moderation (wasatiyyah) by promoting the value of tasamuh (tolerance). This study uses a qualitative method with a library research approach. Data sourced from scientific journals, books, and relevant documents are analyzed using content analysis techniques with a descriptive-critical approach to obtain an in-depth picture of the phenomenon being studied. The results of the study show that the roots of extremism are complex, covering ideological, theological, socio-political, and psychological factors. The most prominent deviation in faith is found in the takfiri view (easily accusing others of heresy), which directly threatens unity. The main solution offered is the strengthening of religious moderation that balances between ukhuwah Islamiyah (Islamic brotherhood) and ukhuwah wathaniyah (national brotherhood). The novelty of this research lies in the integration of the value of ukhuwah wathaniyah as a theological foundation in maintaining national harmony amid the tide of radicalism. The policy implication is the importance for the government and educational institutions to mainstream religious moderation curricula and strengthen inclusive religious literacy in order to counter the spread of extremist ideas at the grassroots level.